FARMERS’ PERSPECTIVE ABOUT THE QUALITY, QUANTITY, AND PACKAGING EFFICIENCY OF PADDY STRAW MUSHROOMS (Volvariella volvacea): A STUDY IN DIFFERENT ZONES OF ODISHA - Kumar Tripathy, Shreemanta; Majhi, Priti Ranjan (The journal of contemporary issues in business and government, 2022)
Nowadays, mushroom cultivation is one of India's most productive and profitable businesses and encourages employment. It is getting popular gradually because, in a short time, it converts farmers' hard work into a remarkable profit. Despite a favorable climate and low-cost labour, India has witnessed a lukewarm response in its growth. At present, India's total production of mushrooms is 0.13 million tons. The paddy straw mushrooms stand sixth among the mushrooms, biologically known as Volvariella volvacea. These edible mushroom cultivated and consumed extensively in Asian continents all throughout. Often these are available in fresh conditions in the regions they are produced. Still, their quality, quantity, and packaging efficiency while reaching the customers is a significant concern for this sector's profitability and sustainable growth. India is reported a lukewarm response in its development, so has Odisha. A nondescript village, Kutenpadar in Odisha's Kalahandi, reputed for starvation death in the '80s, is now a role model for socio-economic growth and women empowerment. However, scientific understanding still has a long way to go! The current study was conducted via questionnaire among farmers in four zones of Odisha. To infer the zonal variation of Odisha in terms of quality, quantity, and packaging efficiency, rigorous statistical analysis such as significance test, ANOVA, and post hoc testing were used. The four zones have considerable differences in quality, quantity, and packaging efficiency, with packaging efficiency being the main reason.